(untitled) (Al-Qamar, 2020)
According to Ahl as-Sunnah wa’l-Jama’ah, the Meezan is truth and it is proven by the Qur’an and the hadiths. While the Mu’tazilites deny the weighty deeds, according to him, it is against the intellect. Actions are objections and weighing objections is not accepted by the intellect On the Day of Resurrection, the great commentators and narrators have stated about three forms of weighty deeds: 1.The book of Acts will be weighed.2. Individuals will be weighed. 3. Deeds will be weighed. Assuming that our deeds will have weight on the Day of Resurrection, it is obligatory to believe in it. It is not necessary for us to know this fact, it will be enough that our deeds will have weight, if the scale of good deeds is heavy then we will be entitled to reward, the scale of bad deeds will be heavy then we will deserve punishment, except that Allah If Allah forgives someone by His grace, it is a different matter.